A Case of Ovarian Actinomycosis. Issue 3 (2003) - Iwasaki, Masahiro; Nishikawa, Akira; Akutagawa, Noriyuki; Fujimoto, Takashi; Teramoto, Mizue; Kudo, Ryuichi
Abstract : Background: Pelvic actinomycosis is uncommon and often presents as a complication of an intrauterine device (IUD). A diagnosis of actinomycosis can be made from the finding of sulfur granules within inflammatory exudate on histologic examination after surgery. However, it may be possible to diagnose actinomycosis before surgery by finding Actinomyces -like organisms on Papanicolaou smears. Case: A 41-year-old woman had been diagnosed as having a pelvic abscess, and bilateral salpingo-oophorectomy was performed. She had been an IUD user for 6 years. Actinomyces -like organisms were detected in her previous Papanicolaou cervical smears. If the patient had been treated when the Actinomyces -like organisms were detected by Papanicolaou smears, the serious ovarian actinomycosis might have been avoided. Conclusion: We suggest that routine cervical examinations are important for women who are IUD users.